Reach and effectiveness of a centralized navigation program for patients with positive fecal immunochemical tests requiring follow-up colonoscopy - Meghan C. O'Leary; Daniel S. Reuland; Connor Randolph; Renée M. Ferrari; Alison T. Brenner; Stephanie B. Wheeler; Deeonna E. Farr; Michael K. Newcomer; Seth D. Crockett (Preventive Medicine Reports, 2023)
Completion rates for follow-up colonoscopies after an abnormal fecal immunochemical test (FIT) are suboptimal in federally qualified health center (FQHC) settings. We implemented a screening intervention that included mailed FIT outreach to North Carolina FQHC patients from June 2020 to September 2021 and centralized patient navigation to support patients with abnormal FITs in completing follow-up colonoscopy. We evaluated the reach and effectiveness of navigation using electronic medical record data and navigator call logs detailing interactions with patients. Reach assessments included the proportion of patients successfully contacted by phone and who agreed to participate in navigation, intensity of navigation provided (including types of barriers to colonoscopy identified and total navigation time), and differences in these measures by socio-demographic characteristics. Effectiveness outcomes included colonoscopy completion, timeliness of follow-up colonoscopy (i.e., within 9 months), and bowel prep adequacy. Among 514 patients who completed a mailed FIT, 38 patients had an abnormal result and were eligible for navigation. Of these, 26 (68%) accepted navigation, 7 (18%) declined, and 5 (13%) could not be contacted. Among navigated patients, 81% had informational needs, 38% had emotional barriers, 35% had financial barriers, 12% had transportation barriers, and 42% had multiple barriers to colonoscopy. Median navigation time was 48.5 min (range: 24–277 min). Colonoscopy completion differed across groups – 92% of those accepting navigation completed colonoscopy within 9 months, versus 43% for those declining navigation. We found that centralized navigation was widely accepted in FQHC patients with abnormal FIT, and was an effective strategy, resulting in high colonoscopy completion rates.